Revealing the Complexity of Polysaccharides: Advances in NMR Spectroscopy for Structural Elucidation and Functional Characterization - Yaqin Liu; Lina Gao; Zeling Yu (Applied Sciences)
Polysaccharides are important biomolecules, which play a key role in biological, medical, and industrial processes due to their diverse structures and important functions. This paper looks into the significant progress made in the structural and functional analysis of polysaccharides by nuclear magnetic resonance (NMR) spectroscopy. NMR spectroscopy, including solution-state and solid-state technology, has revolutionized this field through detailed molecular insights into the structure, conformation, and dynamics of polysaccharides at the molecular level. There have been some important historical breakthroughs in 1D and 2D NMR, which have led to modern methods like multidimensional NMR and nuclear dynamic polarization (DNP). These modern methods offer a high level of resolution and sensitivity and have made it easier to come up with innovative applications. The applications range from the structural elucidation of microbial and plant structures of polysaccharides to improving food texture, developing therapies, and creating sustainable materials. Despite challenges such as signal overlap and limited sensitivity, emerging solutions are making significant progress. Computational modeling, isotope labeling, and integrated methods that combine complementary technologies are driving the boundaries of polysaccharide research. This review demonstrates the transformative role of NMR in revealing the complexity of polysaccharides and its potential to promote future discoveries and new ideas in the dynamic field.